Manipulation of defect state emission in Zn chalcogenide quantum dots and their effects on chlorophyll spectral response - Ibis, Ozge; Uk, Nida; Nar, Ilgin; Unlu, Caner (Elsevier BV, 2025)
Water soluble Zn based quantum dots (QDs) are of interest due to their biocompatibility and less toxic features. They have been frequently used in studies related to biotechnology, especially in agriculture studies. However, to control the optical properties of Zn based QDs has still been a challenge. In this work, the defect state emission of ZnSe QDs was successfully controlled through two different routes; 1) By creating a sulfur rich outer region around the Se rich core 2) By changing the capping agent. Gradient alloyed ZnSeS QDs with Se rich core and S rich outer region were successfully synthesized with two different capping agents; N-Acetyl-L-Cysteine (NAC) and 3-Mercaptopropionic Acid (3-MPA). The contribution of emission originated from surface-defects almost disappeared in NAC capped ZnSeS QDs, with causing a significant increase in photoluminescence quantum yield. The interaction between Zn based QDs with chlorophyll molecules was also investigated. The absorption capacity of chlorophylls significantly enhanced upon interaction with 3-MPA capped ZnSeS QDs. Also, the spectral response of chlorophylls could be modulated through interaction with 3-MPA capped ZnSeS QDs, which could be manipulated by using ZnSeS QDs with different chemical composition. Our results indicated that ZnSeS QDs have potential to be used in agriculture, which could act as a modulator of light-harvesting capacity of chlorophylls. The ability to modulate chlorophyll spectral responses through QD interaction opens new possibilities for optimizing light utilization in photosynthetic organisms, thereby contributing to enhanced crop yields and more efficient use of light energy in natural and artificial ecosystems.